Identifikasi dan Kekerabatan Rhizobia Pohon Mangium dan Sengon Berdasarkan nodD1 dan nifH - Misbakhul Bait; Rumella Simarmata; Rahayu Widyastuti (Jurnal Ilmu Pertanian Indonesia, 2022)
Rhizobia from legumes Acacia mangium (Mangium) and Paraserianthes falcataria (Sengon) have often been isolated and studied for their applications to plants, but studies on the nod and nif genes are still lacking. Even though this plant were often used as a source of paper raw materials and reforestation plants. The aim of this study was to define the genetic relationship of a group of potential strains isolated from tropical legume trees in terms of 16S rRNA, nodD1, and nifH genes. This research method includes the selection of isolates based on the main character of Rhizobiales, to isolate the 16S rRNA, nodD1, and nifH genes from the selected isolates, and to construct a phylogeny tree based on the isolated genes. Two rhizobia were selected based on a selection test, namely DCM 212 from A. mangium and DF13 from P. falcataria. DCM 212 isolate was identified as having the closest similarity to Rhizobium multihospitium CC-13H. The isolate of DF13 had high similarity with Bradyrhizobium elkanii based on 16S rRNA, nodD1, and nifH. The degenerative primer pairs used in this study could not detect nodD1 gene from DCM 212 isolate. Keywords: Bradyrhizobium, phylogeny, rhizobium